Bio-hydrogen production by dark anaerobic fermentation of organic wastewater - Qu, Xinghong; Zeng, Hongxue; Gao, Yongsheng; Mo, Tiande; Li, Yu (Frontiers in Chemistry, 2022)
Using organic wastewater to produce hydrogen by fermentation can generate clean energy while treating wastewater. At present, there are many inhibitory factors in the hydrogen production process, resulting in unsatisfactory hydrogen yield and hydrogen concentration during the fermentation process, and there are still great obstacles to the industrial promotion and commercial application of organic wastewater fermentation hydrogen production. This paper summarizes the hydrogen production of organic wastewater anaerobic fermentation technology. The current anaerobic fermentation hydrogen production systems and technologies are summarized and compared, and the factors and potential conditions that affect the performance of hydrogen production are discussed. The further requirements and research priorities for the market application of fermentation biohydrogen production technology in wastewater utilization are prospected.